Common National Socialist State: A Methodological Problem - Gasiūnas, Adolfas (Problemos, 1981)
The methodological inconsistency of using the concept Dictatorship of the pro 1etariat results in a methodological inconsistency in explaining the process of development of a Dictatorship of the proletariat state into a common national one. This inconsistency is conditioned by the fact that Dictatorship of the pro1etariat is sometimes identified with the formal institutions and methods of government of a socialist state. Dictatorship of the proletariat denotes class contents of a state under socialist economic structure of society. Thus, the development of a Dictatorship of the pro1etariatstate into a common national one may be explained but on an objective ground, i.e., basing on the development of economic structure of a socialist society.